Proinflammatory Polyphosphate Increases in Plasma of Obese Children with Insulin Resistance and Adults with Severe Type 2 Diabetes (2022)
Obesity increases the risk of insulin resistance and type 2 diabetes through increased inflammation at cellular and tissue levels. Therefore, study of the molecular elements involved in obesity-related inflammation may contribute to preventing and controlling it. Inorganic polyphosphate is a natural phosphate polymer that has recently been attracting more attention for its role in inflammation and hemostasis processes. Polyphosphates are one of the main constituents of human platelets, which are secreted after platelet activation. Among other roles, they interact with multiple proteins of the coagulation cascade, trigger bradykinin release, and inhibit the complement system. Despite its importance, determinations of polyphosphate levels in blood plasma had been elusive until recently, when we developed a method to detect these levels precisely. Here, we perform cross sectional studies to evaluate plasma polyphosphate in: 25 children, most of them with obesity and overweight, and 20 adults, half of them with severe type 2 diabetes. Our results show that polyphosphate increases, in a significant manner, in children with insulin resistance and in type 2 diabetes patients. As we demonstrated before that polyphosphate decreases in healthy overweight individuals, these results suggest that this polymer could be an inflammation biomarker in the metabolic disease onset before diabetes.